2022
DOI: 10.3389/fnut.2022.916678
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Farmers Contribution to Food Production in Nigeria

Abstract: Several studies have shown that smallholder farmers produce most of the food in low-income and developing countries and form the backbone of the country’s food supply. This study examines the extent these smallholder farmers in Nigeria can put the country on the path to self-sufficiency and ensure satiety for household food consumption through their local production. The study also examines food production and their resulting yield based on crop production and harvested area, as well as the percentage of crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These thresholds are larger than the very small (<0.64 ha) and small field (0.64 -2.56 ha) classifications where the majority (87%) of Nigeria's fields were captured, according to Lesiv et al (2019). The occurrence of larger field sizes in our study region can be attributed to the emergence of step-up farmers, i.e., smallholder farmers who expanded their farming operations from small to medium-sized fields and the influx of step-in farmers, i.e., diaspora investments in the agricultural sector associated with increasing agri-businesses (Chiaka et al, 2022). Chiaka et al (2022) found a proportional increase in medium-and large-sized farms in Nigeria between 2015 and 2018.…”
Section: Relating Field Size To Cropping Systemsmentioning
confidence: 83%
See 1 more Smart Citation
“…These thresholds are larger than the very small (<0.64 ha) and small field (0.64 -2.56 ha) classifications where the majority (87%) of Nigeria's fields were captured, according to Lesiv et al (2019). The occurrence of larger field sizes in our study region can be attributed to the emergence of step-up farmers, i.e., smallholder farmers who expanded their farming operations from small to medium-sized fields and the influx of step-in farmers, i.e., diaspora investments in the agricultural sector associated with increasing agri-businesses (Chiaka et al, 2022). Chiaka et al (2022) found a proportional increase in medium-and large-sized farms in Nigeria between 2015 and 2018.…”
Section: Relating Field Size To Cropping Systemsmentioning
confidence: 83%
“…Despite intercropping being the dominant agricultural practice among smallholder farmers in Nigeria, as elsewhere in Africa where small-and large scale commercial monocropping systems using mechanization are emerging (Muyanga et al, 2019; Omotilewa field size is increasing (Ibrahim et al, 2021;Chiaka et al, 2022). Using the classes in the global study of field size distribution (Lesiv et al, 2019), Nigeria has 56% of very small fields (<0.64 ha), 31% small fields (0.64 -2.56 ha), 11% medium fields (2.56 -16 ha), 2% large fields (16 -100 ha) and 1% very large fields (>100 ha).…”
Section: Introductionmentioning
confidence: 99%
“…The food system represents an interdependent chain of activities involving production, processing and distribution, and consumption which aim to bring satisfaction to human needs [1,2] . Smallholder farming plays a pivotal role in the food systems and agrarian landscape in Nigeria [3] , especially in south-west Nigeria. The region, consisting of states such as Osun, Oyo, Osun, Ekiti, Ondo and Lagos, is characterized by a predominantly agricultural economy with a significant portion of the population engaged in small-scale farming activities (smallholders) [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…The small-scale farmers in sub-Saharan region of Africa produced the bulk of the food consumed in the region (Chiaka et al, 2022;Okou et al, 2022;Baptista et al, 2022;Akpan & Effiong, 2022). The technique of production used by these farmers in the region is far remoted compared to the methods of production employed in other regions of the World (Ogunkoya et al, 2015;Baptista et al, 2022).…”
Section: Introductionmentioning
confidence: 99%